BIOSORPTION OF METHYLENE BLUE BY SPENT BIOMASS OF Aspergillus terreus USING RESPONSE SURFACE METHODOLOGY - V. SRIDEVI (International Journal of Pharma and Bio Sciences, 2013)
Dye concentration of waste water can lead to a variety of problem. Biosorption has been proved to be a well established and cheap pollutant removal process among other purification techniques in this study our aim is to find the optimization of methylene blue by the spent biomass of Aspergillus terreus using response surface methodology. The spent biomass was received as a free sample from Krebs Bio chemicals Limited, which was the discarded biomass from their Lovastatin production plant. Box- Behnken design will be applied with 3 variables (dye concentration, adsorbent dosage and pH) in the chosen range so as to locate the optimal settings of the chosen variables. The spent biomass of Aspergilus terreus was found to be a potential low-cost biosorbent for the removal of methylene blue from water with a biosorption removal capacity of 94%. Box-Behnken design of RSM was proved to be a convenient tool for optimizing the biosorption process of dye removal, predicting a maximum methylene blue removal of 94% with the optimum process variables being found at 2.1 mg/100ml of initial methylene blue conc., 1.26 gm of adsorbent(A. terreus) dosage/100 ml solution, and a pH value of 7.9.